The ubiquitin specific protease-4 (USP4) interacts with the S9/Rpn6 subunit of the proteasome (2012)
The proteasome is the major non-lysosomal proteolytic machine in cells that, through degradation of ubiquitylated substrates, regulates virtually all cellular functions. Numerous accessory proteins influence the activity of the proteasome by recruiting or deubiquitylating proteasomal substrates, or by maintaining the integrity of the complex. Here we show that the ubiquitin specific protease (USP)-4, a deubiquitylating enzyme with specificity for both Lys48 and Lys63 ubiquitin chains, interacts with the S9/Rpn6 subunit of the proteasome via an internal ubiquitin-like (UBL) domain. S9/Rpn6 acts as a molecular clamp that holds together the proteasomal core and regulatory sub-complexes. Thus, the interaction with USP4 may regulate the structure and function of the proteasome or the turnover of specific proteasomal substrates. © 2012 Elsevier Inc.